Changes in species occurrence and phytomass after clearfelling, prescribed burning and slash removal in two Swedish spruce forests - Nykvist, Nils (1997)
In two old Norway spruce stands, the one at Garpenberg in middle Sweden, the other at Flakaträsk in northern Sweden, the phytomass of the field- and ground-layer was measured before clearfelling and one and four years later. The phytomass of the field-layer was also measured 10 and 16 years after clearfelling. Of 13-14 plant species originally in the field-layer, 2-3 were not found after clearfelling. In contrast, 15 and 9 new species appeared on the plots on which slash was left, at Garpenberg and at Flakaträsk. Some were short-lived, and 16 years after clearfelling, only 11 and 7; respectively, persisted. Corresponding figures for the plots from which slash was removed were 9 and 8; and for the burnt plots 11 and 9. Clearfelling of the old forests at Garpenberg and Flakaträsk also increased the phytomass of the field-layer. Removal of slash decreased the phytomass of some species, increased it for others. During the first few years after burning, phytomass on the burnt plots was less than that on the controls, but three years later it was similar to that on the unburnt plots. The spatial variation in phytomass was great, and no significant difference was found between treatments after clearfelling. The biomass of the most common moss species of Swedish coniferous forests declined strongly after clearfelling. Two new mosses appeared on the clearfelled plots, viz. Polytrichum spp. and Ceratodon purpureus; the latter being found only on burnt plots at Flakaträsk four years after burning.